2018
DOI: 10.1177/0961203318789788
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and prognostic factors in Chinese patients with systemic lupus erythematosus

Abstract: Objectives To investigate the mortality and causes of death in Chinese patients with systemic lupus erythematosus. Methods We collected the clinical data of all consecutive adult systemic lupus erythematosus patients at the Rheumatology department of Peking University First Hospital between January 2007 and December 2015. The primary causes of death were identified, the standardized mortality ratio and years of life lost were calculated, and the survival and variables associated with mortality were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 44 publications
3
36
0
1
Order By: Relevance
“…Our finding that 39% of youth who died had infectious diseases as their primary diagnosis demonstrates once again that infection is a major complication of the rheumatic diseases. The rate of infection we found was higher than reported by Butt et al in a Danish cohort with systemic sclerosis [37] and by Aggarwal et al in an Indian cohort of youth with lupus [38] but similar to the Chinese lupus cohort of all ages by Mu et al [39] We also found that patients with vasculitis and scleroderma were at higher risk of dying in the hospital relative to patients with other rheumatic diseases (of which lupus was the most frequent comparator diagnosis). While this can be explained by the increased severity of these diseases, they are understudied in the transition literature [40,41].…”
Section: Discussionsupporting
confidence: 73%
“…Our finding that 39% of youth who died had infectious diseases as their primary diagnosis demonstrates once again that infection is a major complication of the rheumatic diseases. The rate of infection we found was higher than reported by Butt et al in a Danish cohort with systemic sclerosis [37] and by Aggarwal et al in an Indian cohort of youth with lupus [38] but similar to the Chinese lupus cohort of all ages by Mu et al [39] We also found that patients with vasculitis and scleroderma were at higher risk of dying in the hospital relative to patients with other rheumatic diseases (of which lupus was the most frequent comparator diagnosis). While this can be explained by the increased severity of these diseases, they are understudied in the transition literature [40,41].…”
Section: Discussionsupporting
confidence: 73%
“…Lymphopenia and hemolytic anemia are common hematologic manifestations and one of biomarkers for disease activity or prognosis of SLE (Mu et al 2018). Hemoglobin levels are decreased through the complicated ways including hemolysis, iron deficiency or chronic inflammation, could represent disease status in chronic inflammatory disease.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the normal immune cells are also disproportionately affected, which in turn might increase the patient's susceptibility to infection [3,4]. Indeed, it has been reported widely by clinical studies that severe infection is the leading cause of death in patients with autoimmune diseases, which was partly due to the long-term usage of immunosuppressive drugs [5][6][7]. Thus, new drugs or therapy which is less deleterious to patients' normal immune responses is in urgent need.…”
Section: Introductionmentioning
confidence: 99%